By the danced movement: A gestology of twitch (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article proposes to think the movement of improvisation in dance with repetitive movement, more specifically from twitches, in this case, coming from Tourette's Syndrome in an exercise of crossing aspects of both dance in relation to twitch, and twitch with dance. How dance, as a practice and thought, could be challenge by the sensorimotor perception of twitch? For this, the focus is the relationship between sensory perception and the creation of the gesture, by provoking a principle of definition for a gestology of twitch from the perspective of the dance movement.
Keywords: Tourette's syndrome; Gestology; Improvisation in dance